2015
DOI: 10.1016/j.immuni.2015.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Affinity Maturation of a Potent Family of HIV Antibodies Is Primarily Focused on Accommodating or Avoiding Glycans

Abstract: SUMMARY The high mannose patch on the HIV-1 Envelope (Env) glycoprotein is the epicenter for binding of the potent broadly neutralizing PGT121 family of antibodies, but strategies for generating such antibodies by vaccination have not been defined. We generated structures of inferred antibody intermediates by X-ray crystallography and electron microscopy to elucidate the molecular events that occurred during evolution of this family. Binding analyses revealed that affinity maturation was primarily focused on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
308
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(320 citation statements)
references
References 36 publications
(74 reference statements)
11
308
0
1
Order By: Relevance
“…While the V3-glycan epitope centers on the glycan at N332, high-mannose glycans at other positions can variably be involved in the bnAb epitope (4649). Such diversity is reflected in crystal and electron microscopy structures by different angles of approaches of individual V3-glycan bnAbs (24, 28,45,46,4850) (Wilson and Ward, this volume).…”
Section: Characteristics Of Broadly Neutralizing Antibodiesmentioning
confidence: 99%
“…While the V3-glycan epitope centers on the glycan at N332, high-mannose glycans at other positions can variably be involved in the bnAb epitope (4649). Such diversity is reflected in crystal and electron microscopy structures by different angles of approaches of individual V3-glycan bnAbs (24, 28,45,46,4850) (Wilson and Ward, this volume).…”
Section: Characteristics Of Broadly Neutralizing Antibodiesmentioning
confidence: 99%
“…Single-particle electron microscopy (EM) structures of recombinant native-like soluble Env gp140 trimers (SOSIPs) confirmed that they can adopt the same closed and open architectures as virion-bound Env trimers (5-7), thus the SOSIP substitutions (introduction of a disulfide bond linking gp120 to gp41 and an Ile→Pro mutation in gp41; ref. The closed conformation of HIV-1 Env is stabilized by interactions at the trimer apex mediated by the gp120 V1V2 loop (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). In the closed state, the V1V2 region shields the binding site for the coreceptor on the V3 loop (11, 16), but V1V2 interactions with V3 cannot be maintained when the gp120 protomers rotate and separate to create the CD4-bound open conformation.…”
mentioning
confidence: 99%
“…The HIV-1 Env trimer was regarded as a difficult target for crystallization, as depending on the viral strain it contains 30 AE 3 PNGSs per subunit. Thus, the first crystal structures of the HIV-1 Env trimer were derived from proteins produced in high-mannoseonly forms that were usually further deglycosylated (Julien et al, 2013;Pancera et al, 2014;Scharf et al, 2015;Garces et al, 2015;Stewart-Jones et al, 2016). However, we recently showed that it is possible to obtain crystal structures of fully and natively glycosylated HIV-1 Env trimers despite using trimers containing both complex-type and high-mannose glycans .…”
Section: Discussionmentioning
confidence: 99%
“…Apart from two exceptions (Scharf et al, 2015;Stewart-Jones et al, 2016), previous HIV Env trimer crystal structures used proteins produced in cells that attached only high-mannosetype N-glycans (Julien et al, 2013;Pancera et al, 2014;Scharf et al, 2015;Garces et al, 2015;Stewart-Jones et al, 2016) that were then further enzymatically trimmed to reduce the glycans to single N-acetylglucosamines (GlcNAcs) at accessible PNGSs. Our crystals were obtained from a natively glycosylated Env trimer (BG505 SOSIP.664; Sanders et al, 2013) that was prepared from human embryonic kidney cells (HEK 293 6E cells) that attached both complex-type and high-mannose N-glycans.…”
Section: Crystal Structures Of Natively Glycosylated Env Trimer-fab Cmentioning
confidence: 99%
See 1 more Smart Citation